Bahasa Visual Anak dalam Karya Seni Kaligrafi pada Anak-anak di Desa Tanjungrejo - Kholilur Rohmah; Deka Setiawan; Nur Fajrie (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Calligraphy artwork includes fun learning, which is none other than visual learning by using pictures (visual literacy). The purpose of this study is to find out the process, results and values contained in children's visual language in calligraphy artwork for children in Tanjungrejo Village. This study uses a type of qualitative research with narrative analysis. The location of this research was at the residence of Mr. I, which was a place to recite the Koran for children in Tanjungrejo Village, especially in Beji Kauman Hamlet, to be precise, in Rt 03 Rw 10, Jekulo District, Kudus Regency. The primary data sources are teachers and children who recite the Koran at the place of recitation in Tanjungrejo Jekulo Kudus Village. Secondary data sources come from research documentation, field notes and other supports. Data collection techniques used in this study were observation, interviews and documentation. Data analysis used in this research is data reduction, data presentation and verification. Based on the results of the research and discussion conducted, it can be concluded that the visual language of children's calligraphy artwork in Tanjungrejo Village can be further improved. This is because in making works children are able to pay attention to several elements of works of art and design principles. With this research, it can foster self-confidence from children towards their work. self-confidence can support children's social development which can affect other developments, be it cognitive, physical-motor, language, social-emotional, etc